Bone regeneration in critical‐sized bone defect enhanced by introducing osteoinductivity to biphasic calcium phosphate granules. Issue 3 (11th March 2016) - Wang, D.; Tabassum, A.; Wu, G.; Deng, L.; Wismeijer, D.; Liu, Y.
Abstract: Objectives: Biphasic calcium phosphate (BCP) is frequently used as bone substitute and often needs to be combined with autologous bone to gain an osteoinductive property for guided bone regeneration in implant dentistry. Given the limitations of using autologous bone, bone morphogenetic protein‐2 (BMP2)‐coprecipitated, layer‐by‐layer assembled biomimetic calcium phosphate particles (BMP2‐cop.BioCaP) have been developed as a potential osteoinducer. In this study, we hypothesized that BMP2‐cop.BioCaP could introduce osteoinductivity to BCP and so could function as effectively as autologous bone for the repair of a critical‐sized bone defect. Materials and methods: We prepared BMP2‐cop.BioCaP and monitored the loading and release kinetics of BMP2 from it in vitro . Seven groups ( n  = 6 animals/group) were established: (i) Empty defect; (ii) BCP; (iii) BCP mixed with biomimetic calcium phosphate particles (BioCaP); (iv) BCP mixed with BMP2‐cop.BioCaP; (v) BioCaP; (vi) BMP2‐cop.BioCaP; (vii) BCP mixed with autologous bone. They were implanted into 8‐mm‐diameter rat cranial critical‐sized bone defects for an in vivo evaluation. Autologous bone served as a positive control. The osteoinductive efficacy and degradability of materials were evaluated using micro‐CT, histology and histomorphometry. Results: The combined application of BCP and BMP2‐cop.BioCaP resulted in significantly more new bone formation than BCP alone. The osteoinductive efficacy of BMP2‐cop.BioCaP was comparable to the golden standard use of autologous bone. Compared with BCP alone, significantly more BCP degradation was found when mixed with BMP2‐cop.BioCaP. Conclusion: The combination of BCP and BMP2‐cop.BioCaP showed a promising potential for guided bone regeneration clinically in the future.